Sharia Bank Health Management Strategy (Study On PT. BPRS Carana Kiat Andalas) - Mariko, Suhatri; Prawira, Adi; nasfi, nasfi (International Journal of Indonesian Business Review, 2022)
This study discusses the Sharia Bank Soundness Management Strategy, the research site of PT. BPRS Carana Kiat Andalas in West Sumatra from March 2021-June 2021. The problem is that the Bank's Health Level is decreasing, especially the ratio of CAR, NPF, BOPO and ROA. This type of quantitative descriptive research with research techniques with descriptive analysis method, data collection techniques with interviews and the website of the Financial Services Authority. From the 2014 financial data, it was found that the CAR position was 3.13% and far below the regulatory requirements, the NPF position was 45.38%, the BOPO position was 110.56% and ROA minus 6.45%. The results of the strategic research conducted by Management in improving the soundness of banks within a period of 5 (five) years from 2014 to 2019 include increasing cash capital with new investors, increasing the settlement of non-performing financing and increasing the role of the internal management function. Based on the strategy carried out, it resulted in the position of the bank's soundness level at the end of 2019 with a CAR position of 20.66%, NPF of 10.34%, BOPO of 86.18% and ROA of 1.95%.